Assessment for learning at institutions of higher education: A study of practices among academicians - Nordin, Mohamad Sahari; Zubairi, Ainol Madziah; Ibrahim, Mohd Burhan; Nik Abdul Rahman , Nik Suryani; Abdul Rahman, Zainurin; Othman, Joharry; Tunku Ahmad, Tunku Badariah; Mohd Nor, Zainab (2013)
Assessment for learning is a catalyst for reformation in instructional practices (Sahari, 1999), bridges theory and practices (Riley & Stern, 1998), and creates "a shared academic culture dedicated to assuring and improving the quality of higher education" (Ellyn, 2000, p. 2). This paper presents the findings of a national study conducted at higher learning institutions in Malaysia to find out instructor's self-reported practice, and their perceived competence in assessment for learning. Guided by the frameworks on standards in assessment practices and previous studies in assessing teachers' practices in assessment, this study initially adapted a questionnaire based on five standards in assessment practices from the body of literature. The 23 items questionnaires were distributed to over one thousand instructors from thirty three public and private higher learning institutions in the country. The one thousand and sixty four responses to the questionnaires were subjected to both the principal component analysis and structural equation modeling. The principal component analysis indicated that there were four underlying dimensions of assessment practice measured by the data, with 15 meaningful items. Further analysis reports the rank-order of the four dimensions of assessments for learning. Finally, the structural equation modeling indicated that there was a profound influence of perceived competency on assessment practices. The findings of this study are related to instructional interventions and trainings at the national level to strengthen and support competency in assessment amongst instructors at higher learning institutions in the country.